(untitled) (International Journal of Language, Literacy and Translation, 2025)
The purpose of this research is to examine the effects of using pictorial concept mapping on the retention of collocations in English as a Foreign Language (EFL) learners. 59 intermediate-level students were randomly assigned to one of the three groups: collaborative pictorial concept mapping (22 students), individual pictorial concept mapping (17 students), and translation (20 students). All groups received the same material and instruction time. Two concept-mapping groups used pictorial concept-mapping techniques, while the translation group memorized collocations with their Farsi equivalents. After ten weeks, an immediate post-test was administered to test the first hypothesis. The results shows that the collaborative concept mapping group performed the best. A delayed post-test was given after three weeks to test the second hypothesis, and the findings indicate that the collaborative pictorial concept-mapping group performed better than the other two groups. This research suggests that using pictorial concept mapping in a cooperative learning environment has a positive impact on the retention of collocations for both short-term and long-term periods.